Retorsi dalam Penyelesaian Sengketa Internasional: Studi Kasus terhadap Konflik Ekonomi AS dan Tiongkok - Nabila, Rahma Fauzia; Aulia, Salwa Diandra; Murfrihah, Wilda Malika; Sintia, Riani (Bulletin of Community Engagement, 2024)
The economic conflict between the US and China that began in 2018 employed tariff retaliation to pressure trade policies. This study aims to evaluate the effectiveness of retaliation in achieving economic and political objectives. A qualitative method with descriptive analysis was used to analyze trade data from the U.S. Census Bureau and USTR. Results show a 16% decline in US imports from China in 2019 and an increase in consumer prices. While retaliation protects domestic industries, its impacts include global supply chain disruptions and diplomatic tensions. In conclusion, retaliation effectively pressures trade but brings significant economic risks, requiring international cooperation for optimal outcomes. Retortion can protect domestic industry while also imposing an economic burden on consumers and producers. Apart from the direct economic impact, the retortion also affected diplomatic relations and political tensions between the two countries. Other case studies such as the European Union's sanctions against Russia show that the effectiveness of retortion depends greatly on the political and economic context of the targeted country